Jean-Alfred Fournier - the founder of the European venereology and dermatology (on the one hundredth death anniversary) - O. A. Kisteneva; V. V. Kistenev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents a life story of a great French dermatologist and venereologist, one of the founders of the theory of syphilis Jean-Alfred Fournier (1832-1914). It provides data on the published works by Jean-Alfred Fournier, some of which earned him a doctoral degree. It also provides data on Fournier's election as a member of the French Academy of Medicine in 1879 as well as on the founding of the French Society of Dermatology and Syphiligraphy by Fournier and other French dermatologists in 1889. The article defines the contribution made by Fournier to the development of venereology and practical medicine in the second half of the 19th century and early 20th century.